2019
DOI: 10.12968/bjhc.2019.0041
|View full text |Cite
|
Sign up to set email alerts
|

Review of medical waste management in Jordanian health care organisations

Abstract: Background/Aims Medical waste, or clinical waste, is generated in hospitals, clinics, and pharmaceutical manufacturing as a result of the diagnosis, treatment and medicine that is being produced across the healthcare system. This waste can have a severe effect on both the environment and population health. Overall, between 75% and 90% of the waste produced by healthcare providers is non-risk general waste or domestic waste. It is therefore mandatory for healthcare organisations to have an effective medical was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…However, developing countries in general have no well‐known established comprehensive medication waste management policy up to this time. A recent study in Jordan has reported that there are no regulations that govern medical waste procedure and that medical waste are handled poorly 29 . Public awareness in developing countries regarding the consequences of improper medication disposal is poor 24 .…”
Section: Introductionmentioning
confidence: 99%
“…However, developing countries in general have no well‐known established comprehensive medication waste management policy up to this time. A recent study in Jordan has reported that there are no regulations that govern medical waste procedure and that medical waste are handled poorly 29 . Public awareness in developing countries regarding the consequences of improper medication disposal is poor 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the results of the current study showed a generation rate (0.5 kg/(bed•day)) that represents a very small number of medical facilities in Iraq, the overall generation rate of medical wastes based on the number of state-owned hospitals in Iraq could range from 3.8 to 4.2 kg/(bed•day) [3]. This amount is higher than the range of 0.6-3.7 kg/(bed•day), which was reported by several studies in other countries in the Middle East region [5,[12][13][14][15]. The Iraqi Ministry of Health and Environment has put general guidelines for hospitals to manage their medical waste.…”
Section: Discussionmentioning
confidence: 95%
“…GARCÍA-UBAQUE; ZAFRA-MEJÍA, TRAN et al, 2019;FARROKHI et al, 2016;ANOZIE, 2017;AHMAD et al, 2019;URIOSTE et al, 2018;MARCZAK, 2016;AUGUSTIN et al, 2016;FARZADKIA et al, 2018;JOVANOVIĆ et al, 2016;GAO et al, 2018;KRISHNAN;DEVAMANI;JAYALAKSHMI, 2015;OLIVEIRA;VIANA;CASTAÑON, 2018;PRAYITNO et al, 2018;THANH et al, 2016;SREEREMYA;RAJIV, 2017;NOGUEIRA et al, 2018;KUCHIBANDA;MAYO, 2015;YOUSEFI;AVAK ROSTAMI, 2017;NEVEU C;MATUS C, 2007;AL-MOMANI et al, 2019;PACHAURI et al, 2019;AFOLABI et al, 2018;DEWI et al, 2019;NJUANGANG;LIYANAGE;AKINTOYE, 2018;KIM et al, 2018;MUKHAIBER, 2017;JASEM;JUMAHA;GHAWI, 2018;GARIBALDI et al, 2017;NAMBURAR et al, 2018).…”
Section: Resultados E Discussõesmentioning
confidence: 99%